KONSEP DESAIN KAPAL UDARA SEBAGAI TRANSPORTASI MASSAL UDARA DI WILAYAH JABODETABEK - Riyan Eko Prasetiyo; Michael Tobing; Sovian Aritonang; Novsky Asmoro; Gita Amperiawan (FTK UNSURYA, 2023)
The existing mass transportation cannot accommodate Jakarta’s population increase. The Central Statistics Agency stated that the number of vehicles in Jakarta in 2022 was 26.370.535. The high level of vehicle mobilization results in vehicle congestion in Jakarta. For this reason, it is necessary to have a mode of mass transportation to be a solution to solving congestion. Airships are air mass transportation with a propulsion system consisting of gas and engines. The design of the mode of transportation is carried out using a quantitative method through a literature review approach and numerical formulation analysis. The resulting airship designs have a capacity of 40 people, a total load of 9764 kg, balloon dimensions of 46 m x 13 m x 18 m, and gondola dimensions of 11 m x 4 m x 2m. This research provides a study of the design of mass transportation modes with air operations, which can be a solution to the congestion that occurs. Can reduce existing congestion with efficient routes for the mobilization process at work time.